(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The study focused on examining the formation processes and stages of development of industrial building architecture in Uzbekistan’s cities. This text discusses the issues surrounding the design of industrial buildings, including the challenges in their architectural development, methods for improving their design, and the key needs for such buildings. Additionally, it presents the scientific foundations for industrial building projects.